2013
DOI: 10.1039/c3dt32348j
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of Mn3O4 nanoparticles in ionic liquids

Abstract: This work describes a simple one-step synthesis of Mn3O4 nanoparticles by thermal decomposition of [Mn(acac)2] (acac = acetylacetonate) using imidazolium ionic liquids (ILs) and a conventional solvent, oleylamine, for comparison. The Mn3O4 nanoparticles were characterized by XRD, ATR-FTIR, TEM, Raman, UV/VIS and magnetometry techniques. The addition of 1-n-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide IL (BMI·NTf2) yielded a smaller particle size (9.9 ± 1.8 nm) with better dispersion and more reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 56 publications
(71 reference statements)
1
26
0
Order By: Relevance
“…To further determine structural information, Raman spectroscopy was performed (Figure b). A very strong band at 644 cm −1 , along with a weak band at 348 cm −1 , are consistent with those reported in the literature for Mn 3 O 4 . The strong band at 640 cm −1 is assigned to the Mn−O breathing vibration of divalent manganese ions in tetrahedral coordination, which is found in the mineral hausmannite.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To further determine structural information, Raman spectroscopy was performed (Figure b). A very strong band at 644 cm −1 , along with a weak band at 348 cm −1 , are consistent with those reported in the literature for Mn 3 O 4 . The strong band at 640 cm −1 is assigned to the Mn−O breathing vibration of divalent manganese ions in tetrahedral coordination, which is found in the mineral hausmannite.…”
Section: Resultssupporting
confidence: 91%
“…Av ery strong band at 644 cm À1 ,a long with aw eak band at 348 cm À1 ,a re consistentw ith those reported in the literature for Mn 3 O 4 . [29,30] The strong band at 640 cm À1 is assigned to the MnÀOb reathing vibration of divalent manganese ions in tetrahedral coordination,w hichi sf ound in the mineral hausmannite. In addition, aDband at 1348 cm À1 and aGband at 1598cm À1 is typical for carbon.…”
Section: Resultsmentioning
confidence: 99%
“…Bussamara et al have performed a comparative study by controlling the synthesis of manganese oxide (Mn 3 O 4 ) nanoparticles using imidazolium ionic liquids and oleylamine (a conventional solvent). They found that smaller sized nanoparticles (9.9 ± 1.8 nm) were formed with better dispersity in ionic liquids than in the oleylamine solvent (12.1 ± 3.0 nm) [ 46 ]. Lazarus et al synthesized silver nanoparticles in an ionic liquid (BmimBF4).…”
Section: Solvent System-based “Green” Synthesismentioning
confidence: 99%
“…In thermal decomposition method, Ahmad Morsali and co-workers [66] used a coordination compound, Mn (pyterpy) (H 2 O) (N 3 ) (NO 3 )) as a precursor dissolved in oleic acid, subjected to thermal decomposition at 320 C for 2h under nitrogen atmosphere to fabricate Mn 3 O 4 nano particles. Additionally, Robert Bussamara and his group [67] have prepared similar tetragonal Mn 3 O 4 in controlled manner using manganese precursor and one of the ionic liquids such as 1-n-butyl-3-methylimidazoliumhexa fluoro phosphate (BMI PF6), 1-n-butyl-3-methylimidazolium tetrafluoroborate (BMI⋅BF4), and 1-n-butyl-3-methylimidazoliumbis(trifluoromethanesulfonyl)imide (BMI⋅NTF2) dissolved in oleylamine solvent. It was noticed that Mn 3 O 4 was formed only in the combination of oleylamine and BMI NTF2 solution but failed to get Mn 3 O 4 nano in other two ionic solutions due to the decomposition of ionic liquid (IL).…”
Section: Ionic Liquid Assisted Mn 3 Omentioning
confidence: 99%